PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN - Robert Jao (P3M STMIK Profesional Makassar, 2016)
The objective of research is to examine whether Corporate Social Responsibility disclosure affects on the profitability performance and firm’s value for three years. Corporate Social Responsibility Index (CSRI) by GRI 3 is used as the proxy of Corporate Social Responsibility disclosure. This population of research is companies registered within mining sector list on Indonesia Stock Exchanges with the period 2011-2013. Sample selection methods using purposive sampling. Analysis of data using simple regression, coefficient determination and t statistical test. This result of the research show that Corporate Social Responsibility disclosure has positive and significant influence on the profitability performance namely ROA, ROE and NPM. So does Corporate Social Responsibility disclosure has positive and significant influence on the firm’s value.